The Effect of Pop Up Book for Students’ on Vocabulary Mastery - nasution, sri wahyuni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Abstract This research was aimed to find out whether learning by using Pop-up book significantly effects on students’ vocabulary, or not. This research is quantitative method in pre experimental method. This research uses one group pre-test and post-test design. The instrument was used test. According to the result of the test, it was found that the students’ score before learning by using pop-up book in SMP Negeri 1 Ujung Batu was classified to enough. The students’ score after learning by using pop-up book in SMP Negeri 1 Ujung Batu was classified as good. So there was a significant effect using Pop-up book on students’ vocabulary Mastery at grade VII SMP Negeri 1 Ujung Batu. Keywords: Pop-up book, Vocabulary Mastery